Effective solution focused coaching: a Q-methodology study of teachers' views of coaching with educational psychologists - Small, Craig (2011)
Stober, Wildflower and Drake (2006) call for coaches to 'begin integrating evidence from both coaching-specific research and related disciplines, their own expertise, and an understanding of the uniqueness of each client...into a coherent body of knowledge that applies to and guides coaching'. This study does this by looking into the work of the Nottinghamshire Solution Focused Coaching team and how teacher coachee view effective coaching. Q-methodology (Stephenson, 1953) is a Quali-quantalogical technique able to describe in detail the range of views around a topic. This research used Q-methodology to examine teacher views on effective Solution Focused Coaching with EPs. By-person factor analysis of the Q-sorts of 27 teachers suggested 3 different viewpoints on effective Solution Focused Coaching (SFC) and some key ideas held in consensus across the views. The viewpoints were found to differentiate across three themes; whether coaching involved developing action plans; where the goals for coaching emanated from; and the coachee's engagement with the confidentiality offered. The consensus statements showed a preference for a focus on strengths, skills, and what is helping at present; of receiving strength-based feedback; and on identifying elements of goals being in place. Working with client strengths has been highlighted in the therapy outcome literature and the study is theorized with reference to this and the concept of "therapeutic alliance". It is suggested that effective SFC might involve the EP constructing a "coaching alliance" and combining this with a focus on client strengths to provide a foundation for SFC. The descriptions of the viewpoints, and consensus ideas, are offered as resources for exploring the practicalities of such an approach. Whilst being the semantic and subjective products of human thought, the views operant in the study can be said to be "as real, as substantial, and as difficult to get around as any thing the natural world puts in our way" (Watts, 2007). Such a linguistic turn is expanded upon through exploration of educational psychology as social construction. Suggestions are made about how EPs could interpret social constructionism in their practice.